Magnetic proline-based ionic liquid surfactant as a nano-carrier for hydrophobic drug delivery. Issue 15 (20th March 2020) - Kulshrestha, Akshay; Gehlot, Praveen Singh; Kumar, Arvind
Abstract : Biofriendly and magnetic proline based ionic liquid surfactant demonstrated for drug delivery system. Abstract : Magnetic proline-based surface-active ionic liquid ([ProC10 ][FeCl3 Br]) have been synthesized and investigated for their application in hydrophobic drug delivery. Hydrophobic drugs lead to poor absorptivity, drug aggregation, and high local toxicity. Herein, the vesicular structures formed from [ProC10 ][FeCl3 Br] have been used as drug delivery reactors. The self-assembly behavior of [ProC10 ][FeCl3 Br] in aqueous medium has been investigated using tensiometry, fluorescence, dynamic light scattering (DLS), and transmission electron microscopy (TEM). The physicochemical interactions of [ProC10 ][FeCl3 Br] with animal DNA have been studied using circular dichroism (CD), fluorescence, zeta potential, and gel electrophoresis to confirm its bio-friendly nature. The engendered vesicles prepared from [ProC10 ][FeCl3 Br] have been investigated for the in vitro drug delivery of guest molecule pyrene as a hydrophobic model drug and ciprofloxacin as a hydrophobic antibiotic drug. The drug loading capacity and spontaneous kinetic release of the drug have been studied using various theoretical mathematical drug release models.